Sistem Informasi Monitoring Pertumbuhan Anak Pada Golden Age Menggunakan Pengukuran Antropometri (Studi Kasus: Posyandu Anggrek XIII Tangerang) - Errina Fadhillah (2020)
The golden period in the process of growing a child is the beginning of a child's life. From birth to two-year-old children, at this age have a sizeable future because it cannot be repeated. For this reason, parents are obliged to increase their growth carefully, one of them is by utilizing Integrated Healthcare Center activities. Posyandu is managed and managed by the community to provide convenience to the community in obtaining health services for children. However, some things can hamper the process at Integrated Healthcare Center, namely, parents do not bring a card to health (KMS) as a medium for recording children's growth, or even KMS is lost and also the child's growth data will be hampered every month. That way the author wants to create a child growth monitoring information system with anthropometric measurement methods, namely child growth can be supported by conducting a growth check consisting of measurements of body weight, height, and head circumference. KMS that has been used so far does not need to use anthropometry so that to complete the contents of the existing KMS, parents are expected to be able to find out complete information on children's growth data. The method used in this study uses the prototyping method because there are data by the needs of anthropometric measurements and in making good communication systems with application users. With this application, the expected results will be built is a web-based application to monitor children's growth regularly and continuously.